2017
DOI: 10.1093/fampra/cmx095
|View full text |Cite
|
Sign up to set email alerts
|

Contextual levers for team-based primary care: lessons from reform interventions in five jurisdictions in three countries

Abstract: BackgroundMost Western nations have sought primary care (PC) reform due to the rising costs of health care and the need to manage long-term health conditions. A common reform—the introduction of inter-professional teams into traditional PC settings—has been difficult to implement despite financial investment and enthusiasm.ObjectiveTo synthesize findings across five jurisdictions in three countries to identify common contextual factors influencing the successful implementation of teamwork within PC practices.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 28 publications
1
65
0
Order By: Relevance
“…Currently, nurse activity in general practices is supported by annual Australian Government funding (Australian Govenment, 2018). While a fee for service funding system operates in Australian primary care, moves towards block funding (McKittrick and McKenzie, 2018) and wider calls to reform to integrative, team orientated models could further enhance the nursing role (McInnes et al, 2016, Russell, 2018.…”
Section: Previous Interventions Have Employed Evidence Based Strategimentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, nurse activity in general practices is supported by annual Australian Government funding (Australian Govenment, 2018). While a fee for service funding system operates in Australian primary care, moves towards block funding (McKittrick and McKenzie, 2018) and wider calls to reform to integrative, team orientated models could further enhance the nursing role (McInnes et al, 2016, Russell, 2018.…”
Section: Previous Interventions Have Employed Evidence Based Strategimentioning
confidence: 99%
“…The nursing workforce in general practice has grown significantly in recent decades along with international recognition that the role could be more fully utilised (Bauer and Bodenheimer, 2017, Halcomb et al, 2014, Merrick et al, 2014. Current models of general practice remain reactive, GP led care (Russell, 2018) with lack of role clarity, suboptimal collaboration and funding mechanisms contributing to the under-utilisation of nurses (Bauer andBodenheimer, 2017, McInnes et al, 2015). Emerging evidence demonstrates nurse-led chronic disease management to be feasible and highly acceptable to consumers (Halcomb et al, 2015a, Halcomb et al, 2015b, Mahomed et al, 2012, Stephen et al, 2018a, Stephen et al, 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the current study, time and space resources were required to ensure team collaboration. This has long been supported by research that shows financial support for team activities has a positive effect on team performance [12,23]. Despite the need for resources to support team activities, results showed that teams and patients perceived that HT was valuable, embedded well into the clinic environment, and worth maintaining.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers have found mixed levels of buy-in for interdisciplinary working by certain team members (i.e., physicians, pharmacists and nurses) with a tendency of physicians to resist collaborative teamwork, giving preference to working independently [23]. Primary care researchers explored contextual factors influencing team performance in five jurisdictions in three countries and found that despite moving to collaborative teams, primary care clinicians still tended to work in parallel, infrequently using team approaches to solve clinical problems [12]. They also found that team-based primary care was enhanced when direct physician involvement was not required in care provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation